2012
DOI: 10.1007/s11010-012-1454-0
|View full text |Cite
|
Sign up to set email alerts
|

HuR–hnRNP interactions and the effect of cellular stress

Abstract: The heterogeneous nuclear ribonucleoproteins (hnRNPs) constitute an important group of RNA-binding proteins (RBPs) that play an active role in post-transcriptional gene regulation. Here, we focus on representative members of the hnRNP group of RBPs, namely hnRNP A1 and hnRNP C1/C2, which participate mainly in RNA splicing, as well as on HuR, a prototype of the AU-rich element-binding proteins (ARE-BP), which has an established role in regulating the stability and translation of target mRNAs. HuR and most hnRNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 51 publications
1
24
0
Order By: Relevance
“…The heterogeneous nuclear ribonucleoproteins (hnRNPs) play an active part in post-transcriptional gene regulation, e.g., RNA splicing and regulation of the stability and translation of target mRNAs. Most hnRNPs are primarily localized in the nucleoplasm, and can shuttle between the nucleus and the cytoplasm [35]. …”
Section: Resultsmentioning
confidence: 99%
“…The heterogeneous nuclear ribonucleoproteins (hnRNPs) play an active part in post-transcriptional gene regulation, e.g., RNA splicing and regulation of the stability and translation of target mRNAs. Most hnRNPs are primarily localized in the nucleoplasm, and can shuttle between the nucleus and the cytoplasm [35]. …”
Section: Resultsmentioning
confidence: 99%
“…hnRNPs include at least 20 discrete hnRNPs that are labeled as hnRNP A through U. These hnRNPs are actively involved in many facets of mRNA metabolism, from transcription to post-transcriptional events and translation (Papadopoulou et al, 2013;Wen et al, 2010). ELAV is another important small family of RBPs that comprises four members: HuR, HuB, HuC, and HuD.…”
Section: Discussionmentioning
confidence: 99%
“…Both hnRNP A1 and HuR are mainly localized in the nucleoplasm. They regulate the stability and translation of target AREcontaining mRNAs and can shuttle between the nucleus and cytoplasm (Brennan and Steiz, 2001;Papadopoulou et al, 2013). In this study, we focused on hnRNP A1 and HuR which are mRNA stabilizing factors that stabilize ARE-containing mRNAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, silencing of PRINS gene resulted in altered HeLa cell morphology and gene expression alterations, among others in the case of G1P3, an interferon-inducible anti-apoptotic gene 34 . It has been reported that long mRNA-like ncRNAs form complexes with proteins [35][36][37] , and act as regulators of various cellular functions 38 . Therefore we have performed an in vitro binding assay which revealed that PRINS interacts physically with the molecular chaperone protein nucleophosmin (NPM, B23) in HaCaT and normal human epidermal keratinocyte (NHEK) lysates and we were first to describe the upregulation of this protein in psoriasis 39 .…”
Section: Non-coding Rnasmentioning
confidence: 99%